A rare cause in etiology of left atrial mass: metastatic testicular germ cell tumor - Huseyin, Serhat (Kardiochir Torakochirurgia Pol, 2016)
Although intracardiac metastasis of germ cell tumors is rare, it can be localized in the right or left heart by disseminating spread and give their cardiac symptoms depending on the location of metastatic mass. We present a 38-year-old male patient with a preliminary diagnosis of testicular tumor who was followed by the medical oncology clinic with cerebrovascular event and heart failure symptoms.